Neonatal protection and preterm birth reduction following maternal group B streptococcus vaccination in a mouse model. (2nd December 2017) - Bernardini, R.; Aufieri, R.; Detcheva, A.; Recchia, S.; Cicconi, R.; Amicosante, M.; Montesano, C.; Rossi, P.; Tchidjou, H. K.; Petrunov, B.; Orefici, G.; Mattei, M.
Abstract: Purpose: Evaluate effects of maternal immunization in a mouse model of Group B Streptococcus (GBS) vaginal colonization using clinical isolates. Materials and methods: Female pregnant mice were immunized with heat-killed GBS 21 days before pregnancy and were inoculated intravaginally with GBS cultures (5 × 10 7 CFU twice a day for three days) from the 16th day of pregnancy. Gestation period and mice survival were monitored. Maternal anti-GBS IgG levels have been determined by ELISA analysis in vaccinated, unvaccinated mothers and newborns. Results: Maternal immunization before pregnancy provided protection to newborns for three of the four GBS strains used. Evaluation of the immunogenicity showed that this vaccination induced higher levels of IgG in vaccinated compared to unvaccinated dams and the presence of antibodies in the offspring at embryonic and postnatal age, and a Th1 response and high levels of IgG2a subclass antibody and IFN-γ were detected. A significant reduction of preterm births was observed in vaccinated mothers ( p < 0.05). Conclusions: Our finding suggest that vaccinated mothers could protect their progeny from GBS infection and preterm birth through passive immunization. The proposed mouse model may represent a noninvasive and effective tool to investigate pathogenetic mechanisms of GBS ascending infection and for vaccine protection studies.